Kekerasan Wanita dalam komik Azumi karya Yuu Koyama - Candra Sari, Made Cindy (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 2 (2020), 2020)
This research’s titled is "Women's Violence in Azumi Comics by Yuu Koyama". This research aims to find out how the forms of female violence in the comic Azumi by Yuu Koyama and what attitudes are shown by women towards violence. This research uses descriptive qualitative method. The research results are, there are five forms of violence against women such as, physical violence, rape, prostitution, sexual harassment and verbal harassment. Also, the attitudes shown by female characters in comics are the strong women and brave women.